An asymptotic analysis of convection in boundary layer flows in the presence of a chemical reaction - Shateyi, S.; Sibanda, P.; Motsa, S.S. (Archives of Mechanics, 2005)
In this study we investigate the stability of two-dimensional disturbances imposed on a boundary layer flow over a semi-infinite flat plate in the presence of a reacting chemical species. Species concentration levels are assumed to be small, what is typical for many processes in water and in atmospheric air. We exploit the multi-deck structure of the flow in the limit of large Reynolds numbers to analyze asymptotically the perturbed flow. The neutral eigenrelations are obtained implicitly and limiting cases for large buoyancy and reaction kinematics are investigated. The results show some interesting effects of the Damkohler number on the wave number and wave speed of the disturbed flow.